Districts on the Edge: The Impact of Urban Sprawl on a Rural Community - Paul Theobald (Journal of Research in Rural Education, 1988)
This paper attempts to capture some of the controversy schools and education experience in rural communities which find themselves on the edge of urban sprawl. As suburbanites settle farther from metropolitan areas, once homogeneous rural communities must open up to new populations. Often, as described here, competing community expectations for schools and schooling clash and students are caught in the middle.